Tislelizumab plus chemotherapy in metastatic extramammary Paget disease after surgery: a case report - Wang, Dongxing; Huang, Chuang; Wang, Dongming (Frontiers in Oncology, 2024)
Extramammary Paget disease (EMPD) is a rare epithelial adenocarcinoma in apocrine-gland rich skin, involving the vulva, the scrotum, and the penis. with distant metastases and a poor prognosis. Local EMPD patients generally have a good prognosis, with expected 5-year survival of 60%–92%, but distant metastasis represents poor prognosis and 5-year survival of 10%. Treatment approaches for advanced EMPD are chemotherapy and biological agents, which carry limited efficacy. We report the case of a 57-year-old man diagnosed with metastatic EMPD, who showed a long-term disease control with a combination therapy (an immune checkpoint inhibitor - tislelizumab plus chemotherapy – paclitaxel albumin and cisplatin). This patient underwent a wide penile scrotal lesion excision and six cycles of tislelizumab plus chemotherapy. The patient achieved partial response for the metastatic lesions according to the Response Evaluation Criteria in Solid Tumors (version 1.1). This case report supports further investigation of the combination treatment of chemotherapy and immune checkpoint inhibitors in the management of metastatic EMPD, which currently has an abysmal prognosis and no standardized treatment.